Does Developmental Aid Impact or Impede on Growth: Evidence from Nigeria - Olanrele, Iyabo A.; Ibrahim, Taofik Mohammed (International Journal of Economics and Financial Issues, 2015)
This paper examines the effect of four different types of developmental aid on economic growth in Nigeria utilizing the Two-Stage Least Square (2SLS) estimation technique between 1970 and 2012. The empirical estimates show that multilateral aid had more impact on growth compared to bilateral aid from Nigerian’s trading partners, top-five CDI ranked countries, and Nordic countries. Our findings support the need for stringent conditionalities and standard monitoring and evaluation framework by donors in order to promote meaningful impact of developmental aid on economic growth. Keywords: Developmental aid; Economic Growth; Nigeria JEL Classifications: O1; O2; O4